‘Psychic Screams’: Reflections on a Howard Thurman Sermon - Lyons, Ivory (Tattva Journal of Philosophy, 2012)
The 20th century mystic/writer Howard Thurman makes a claim that there is a symbiotic relationship between the earth adn humans such that what humans experience as violence against each other is actually a reflection of the violence that humans do to the earth. The major contentions of this paper are (i) the curse as laid out in Genesis assumes that there is an intended harmony between the various elements of creation, but this harmony was disrupted ultimately by human mistrust of the divine; and (ii) that healing is possible if humans learn how to live in peace with the Earth. The paper will also explore possible ramifications for human life and for spiritual life on this plant if indeed this is the sort of harmony envisioned or entrusted to humans, animals and plant life.